Arti Baik Menurut George Edward Moore: Usaha Pemerintah Indonesia Mendukung Perdamaian Rusia-Ukraina: The Meaning of Good by George Edward Moore: The Indonesian Government's Business to Support Russia-Ukraine Peace - Astageni, Empi Siloka (Undiksha, 2024)
The focus of this article is to show the Indonesian government's efforts to support peace between Russia and Ukraine which are currently in conflict. The war between Russia and Ukraine had a serious impact on the lives of the global community. The efforts made by the Indonesian government contain good values in the diplomatic realm. These peace efforts are based on humanitarian grounds. The conflict between Russia and Ukraine has caused many casualties and damage here and there. The author wants to link the Indonesian government's support for peace with the concept of